Evaluasi Pembelajaran Seni Musik pada Materi Teknik Vocal di Kelas VII SMP Negeri 02 Oku - Kholifadya, Aqilma; Heryanto, Heryanto; Hidayatullah, Fadhilah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study was to determine the evaluation of learning the art of music on vocal technique material in Class VII SMP Negeri 02Oku. The focus of this research is on learning the art of music through vocal technique. While the sub-focus of the research is on the evaluation of learning the art of music on vocal technique material: Intonation, Congeniality, Articulation, Breathing. The research problem is how to evaluate the art of music learning on vocal technique material in Class VII SMP Negeri 02Oku. The method used is a qualitative method. The object of this research is Class VII students. Data collection techniques used in this study were observation, interviews, and documentation. The data analysis techniques used in thisstudy include: (1) data reduction, (2) data presentation, (3) data conclusion. Based on the results of the research, it can be concluded that in the evaluation process of vocal technique material in class VII SMP Negeri 02 Okuthe teacher refers to the 2013 curriculum assessment aspects which include cognitive, affective and psychomotor assessments. For cognitive assessment or the value of knowledge, art and culture teachers refer to students' understanding of the material, while for affective or attitudeassessments,subject teachers refer to students' social attitudes during the learning process, and for psychomotor assessments, teachers judge students more based on students' ability to practice techniques. vocals in singing one voice in the form of Unisono.